Evolutionary Relationships of Ljungan Virus Variants Circulating in Multi-Host Systems across Europe - Rossi, Chiara; Zadra, Nicola; Fevola, Cristina; Ecke, Frauke; Hörnfeldt, Birger; Kallies, René; Kazimirova, Maria; Magnusson, Magnus; Olsson, Gert E.; Ulrich, Rainer G.; Jääskeläinen, Anne J.; Henttonen, Heikki; et al.
The picornavirus named ‘Ljungan virus’ (LV, species Parechovirus B) has been detected in a dozen small mammal species from across Europe, but detailed information on its genetic diversity and host specificity is lacking. Here, we analyze the evolutionary relationships of LV variants circulating in free-living mammal populations by comparing the phylogenetics of the VP1 region (encoding the capsid protein and associated with LV serotype) and the 3Dpol region (encoding the RNA polymerase) from 24 LV RNA-positive animals and a fragment of the 5′ untranslated region (UTR) sequence (used for defining strains) in sympatric small mammals. We define three new VP1 genotypes: two in bank voles (Myodes glareolus) (genotype 8 from Finland, Sweden, France, and Italy, and genotype 9 from France and Italy) and one in field voles (Microtus arvalis) (genotype 7 from Finland). There are several other indications that LV variants are host-specific, at least in parts of their range. Our results suggest that LV evolution is rapid, ongoing and affected by genetic drift, purifying selection, spillover and host evolutionary history. Although recent studies suggest that LV does not have zoonotic potential, its widespread geographical and host distribution in natural populations of well-characterized small mammals could make it useful as a model for studying RNA virus evolution and transmission. 2021